1975
DOI: 10.1021/bi00686a007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of formaldehyde on the circular dichroism of chicken erythrocyte chromatin

Abstract: Formaldehyde (HCHO) fixation of chicken erythrocyte chromatin produces a marked decrease in its positive circular dichroism (CD), above 260 nm, and the appearance of s small negative ellipticity around 295 nm. The ultraviolet spectrum of chromatin is unaffected, nor does HCHO produce any changes in the uv or CD spectra of chicken erythrocyte DNA. The extent of the circular dichroism transition from the native chromatin to the suppressed spectrum is dependent on the concentration of HCHO and salt concentration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2

Year Published

1976
1976
1987
1987

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
(43 reference statements)
1
3
2
Order By: Relevance
“…The formatin of crosslinks between histones and DNA results in a conformational change of DNA, which is detectable as a change of positive ellipticity in the region of 250-300 nm. Decrease of positive ellipticity of nucleohistone on reaction with formaldehyde has been reported by Senior and Olins [16], but their results do not agree with our results. They reported that the positive ellipticity above 240 nm progressively decreased with increase in the formaldehyde concentration, finally attaining a negative value with 3 % formaldehyde.…”
Section: Discussioncontrasting
confidence: 99%
“…The formatin of crosslinks between histones and DNA results in a conformational change of DNA, which is detectable as a change of positive ellipticity in the region of 250-300 nm. Decrease of positive ellipticity of nucleohistone on reaction with formaldehyde has been reported by Senior and Olins [16], but their results do not agree with our results. They reported that the positive ellipticity above 240 nm progressively decreased with increase in the formaldehyde concentration, finally attaining a negative value with 3 % formaldehyde.…”
Section: Discussioncontrasting
confidence: 99%
“…Figure 5a shows CD spectrum of native chromatin and that of chromatin treated with formaldehyde either for 1 or 24 h. Formaldehyde treatment causes a permanent decrease and red shift of the positive CD band near 275 nm and a slight decrease in the negative CD band near 220 nm, changes which occur mostly during the first hour of fixation. These results confirm the original observations of Senior and Olins (1975)…”
Section: Resultssupporting
confidence: 92%
“…Only small changes (< 105;;) in the cd spectrum ellipticity at 275 nm bere noted. This is unlike the observations made on chromation in solution (28).…”
Section: Electroiz Microscopycontrasting
confidence: 93%